1981
DOI: 10.1002/eqe.4290090106
|View full text |Cite
|
Sign up to set email alerts
|

Overturning effects in stiffened building frames

Abstract: In this paper seismically induced overturning effects in stiffened building frames are studied by examining the response of two structures: a 20‐storey ‘core wall’ reinforced concrete frame and a 10‐storey steel braced frame. The excitations utilized in the study are the 1971 Pacoima Dam S16E Record and the 1940 El Centro N‐S Record magnified by a factor of two. Non‐linear effects of the following types are considered: plastic hinging of beams and columns, yielding and/or buckling of bracing members and transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Earlier studies on rocking structures (Housner 1963;Meek 1978;Priestley et al 1978;Huckelbridge and Clough 1978;Psycharis and Jennings 1983;Chopra and Yim 1985) have indicated the beneficial role of foundation uplifting on the performance of the supported structure, particularly during severe seismic shaking. Furthermore, allowing for foundation rocking has been proposed by several researchers as an effective method of seismic isolation (Beck and Skinner 1973;Huckelbridge and Ferencz 1981;Priestley et al 1996;Mergos and Kawashima 2005;Chen et al 2006;Sakellaraki and Kawashima 2006) and has been applied in the design of modern bridges (e.g., the Rion Antirion Bridge; Pecker 2005). However, in the last decade, the research community has ventured one significant step further, acknowledging that in a way similar to pure uplifting, concurrent inelastic soil response may also help to protect the superstructure against increased seismic demands (Martin and Lam 2000;Pecker and Pender 2000;Faccioli et al 2001;Gajan et al 2005;Harden et al 2006;Pecker 2005;Gazetas et al 2007;Paolucci et al 2008;Anastasopoulos et al 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies on rocking structures (Housner 1963;Meek 1978;Priestley et al 1978;Huckelbridge and Clough 1978;Psycharis and Jennings 1983;Chopra and Yim 1985) have indicated the beneficial role of foundation uplifting on the performance of the supported structure, particularly during severe seismic shaking. Furthermore, allowing for foundation rocking has been proposed by several researchers as an effective method of seismic isolation (Beck and Skinner 1973;Huckelbridge and Ferencz 1981;Priestley et al 1996;Mergos and Kawashima 2005;Chen et al 2006;Sakellaraki and Kawashima 2006) and has been applied in the design of modern bridges (e.g., the Rion Antirion Bridge; Pecker 2005). However, in the last decade, the research community has ventured one significant step further, acknowledging that in a way similar to pure uplifting, concurrent inelastic soil response may also help to protect the superstructure against increased seismic demands (Martin and Lam 2000;Pecker and Pender 2000;Faccioli et al 2001;Gajan et al 2005;Harden et al 2006;Pecker 2005;Gazetas et al 2007;Paolucci et al 2008;Anastasopoulos et al 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…A few case studies can be found in the literature in which both sources of nonlinearity, that is, inelastic behavior of the structure and the foundation uplift, are taken into account. Examples are the researches of Huckelbridge and Ferencz and Nakaki and Hart who showed that the ductility demand of the structure can be reduced when transient uplift is allowed to occur. Pecker and Chatzigogos came to the same conclusion by employing an IDA method to study the influence of nonlinear foundation behavior on the performance of a nonlinear bridge structure.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years some researchers reported on the base rotating shear walls (1,2,3,4,5). However, the effect of base rotation of a structural wall on the behaviour of a reinforced concrete frame building is not clearly understood although a low-rise wall tends to uplift at its base rather than fail in shear or flexure, especially when the wall is supported on footing foundations.…”
Section: Introductionmentioning
confidence: 99%